Hubungan antara Kecenderungan Internet Addiction dengan Empati pada Anak Sekolah Dasar - Mawarani, Galuh (Cognicia, 2019)
Empathy in children is considered very important because it will affect their social and individual skills. One of the factors that influence the empathy is communication through the internet. The tendency of internet addiction is the use of the internet which is aimed of accessing social media, playing online games, listening to music and videos online excessively. The purpose of this study is to determine the relationship between the tendency of internet addiction and empathy in elementary school children. This study used a correlational qualitative approach. The subjects were 115 students with a range of grades 4 to 6 taken by purposive sampling technique. The method of data analysis was the product moment correlation method from Karl Pearson of utilizing the SPSS 21.0 program. The results showed that (r) mark was 0.206 with p was 0.014 <0.05. It indicated that there is a significant negative relationship between the tendency of internet addiction and the empathy. The contribution of internet addiction to the empathy was 4,2% (r2= 0.042).